Návrh počítačové sítě multimediální domácnosti - Herman, Jaromír (Vysoké učení technické v Brně. Fakulta podnikatelská, 2015)
Předmětem bakalářské práce je návrh počítačové sítě multimediální domácnosti na základě požadavků investora. Bakalářská práce je rozdělena do tří částí. První část obsahuje teoretická východiska problematiky návrhu počítačové sítě. V druhé části je shrnuta analýza nevyhovujícího současného stavu sítě. Poslední část popisuje samotnou realizaci konkrétního návrhu. Součástí práce je také kalkulace nákladů a výkresové dokumentace.

The topic of this bachelor thesis is to design a computer network for multimedial home on the basis of the investor’s requirements. The bachelor thesis is divided into three parts. The first part provides with various possibilities of the computer network design in theory. The second part summarizes an analysis of the current network in its inconvenient state. The last part presents the realization of the particular design itself. The bachelor thesis also contains the project costing and the project drawing documentary materials.
Multimedial Home Computer Network Design
Keywords: Počítačová síť; Univerzální kabeláž; Síťová infrastruktura; LAN síť; Ethernet; Bezdrátová síť; Computer network; Universal cabling; Network infrastructure; LAN network; Ethernet; Wireless network